Insights into the localized corrosion initiation mechanisms of alloy 718 - Julia Botinha; Bodo Gehrmann; Helena Alves; Michael Rohwerder (Heliyon)
Nickel alloys are widely used in the oil and gas industry where high corrosion resistance in chloride water or in sour environments is required. When high mechanical properties are required in combination with high corrosion properties, alloy 718 (UNS N07718) is one of the preferred choices, although it still presents limitations in terms of corrosion resistance in some applications: despite offering outstanding resistance to localized corrosion, alloy 718 is not immune to it. Its high corrosion resistance is mainly due to its high nickel and chromium contents combined with additions of molybdenum and other noble elements. Metallic and non-metallic precipitates are formed during the manufacturing process and each is known to interact with the matrix and the oxide protective film, but there is a lack of studies on the mechanisms that occur during the initiation of localized corrosion in this alloy. In this work, we investigate the localized corrosion initiation process and follow up the first steps of corrosion attack in alloy 718 in a 1M NaCl solution through the combination of microscopy and electrochemical techniques. As a result of potential application in a brine electrolyte, we conclude that nitrides and carbides play an important role on the corrosion initiation.